IDENTIFIKASI KETIDAKPASTIAN DAN HUBUNGANNYA DENGAN PERFORMANSI DI UMKM - HIMADHANI, MAIRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
SMEs make positive contribution to the indonesian economy, especially in increasing GDP (59,17%) and creating jobs (98,23%). Due to itsvital role, Indonesian government facilitates the development of SMEs in Indonesia through various programs such as People Business Credit Program and Commercial loans. In 2012, the number of SMEs in Indonesia has reached 56,534,592 units of the various fields of business and contribute to IDR 1,452,460 billions to the increase of national GDP and absorbs as many as 107,657,509 workers. Based on data from the Indonesian Ministry of Cooperatives and Small-Medium Enterprises, SMEs can increase 10%- 20% of Indonesia's GDP. Due to its vital role, the development and the management of SMEs needs to be focused. But, the development of SMEs is not without problems. One of the major obstacles is relating to supply chain uncertainty. This research aims at exploring supply chain uncertainty in SMEs, evaluating relevant uncertainty factors and its relation to SMEs' performance. Literature review was conducted to identify potential uncertainty and then to build a theoretical framework. Three sources of uncertainty, i.e., internal organization uncertainty, internal supply chain uncertainty and external uncertainty, were investigated. The framework was then against empirical data which were collected through interviews and questionnaires. Sector of clothing and leather was selected due to its highest contribution of total productions, investments and job creation among other sectors in Yogyakarta,Indonesia. Total indicators of 43 were derived from literature review to describe uncertainty factors in company's supply chain. Based on a pilot study with 30 respondents, the indicators were reduced to 20 indicators in SMEs. Due to insufficient content validity ratio, the questionnaire was designed. Data were collected by interview using designed the questionnaire on 102 selected respondents. The respondent was selected using purposive sampling technique based on the place where is to be the center of clothing and leather industry. Some tests that are evaluating data adequacy, outliers, normality and multicolinearity were conducted. Empirical data was analyzed by Exploratory Factor Analysis (EFA) and Structural Equation Modeling (SEM). EFA explores the data and provide the information how many factors are needed to represent the data, CFA is part of SEM to verify the factors that had been built by EFA and structural model determines the relationship between uncertainty and SME's performance. EFA results show that internal organization uncertainty relates to product characteristics, manufacturing process and decision complexity